Blood use and transfusion needs at a large health care system in Washington state during the SARS‐CoV‐2 pandemic. Issue 12 (28th August 2020) - Pagano, Monica B.; Cataife, Guido; Fertrin, Kleber Yotsumoto; Gernsheimer, Terry; R. Hess, John; Staley, Elizabeth; Clark, Christine; Senn, Nina; Tuott, Erin; C. Tsang, Hamilton
Abstract: Background: This report evaluates hospital blood use trends during the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic, and identifies factors associated with the need for transfusion and risk of death in patients with coronavirus 2019 (COVID‐19). Methods: Overall hospital blood use and medical records of adult patients with COVID‐19 were extracted for two institutions. Multivariate logistic regression models were conducted to estimate associations between the outcomes transfusion and mortality and patient factors. Results: Daily blood use decreased compared to pre–COVID‐19 levels; the effect was more significant for platelets (29% and 34%) compared to red blood cells (25% and 20%) at the two institutions, respectively. Surgical and oncologic services had a decrease in average daily use of platelets of 52% and 30%, and red blood cells of 39% and 25%, respectively. A total of 128 patients with COVID‐19 were hospitalized, and 13 (10%) received at least one transfusion due to anemia secondary to chronic illness (n = 7), recent surgery (n = 3), and extracorporeal membrane oxygenation (n = 3). Lower baseline platelet count and admission to the intensive care unit were associated with increased risk of transfusion. The blood group distribution in patients with COVID‐19 was 37% group O, 40% group A, 18% group B, and 5% group AB. Non–type O was not associated with increased risk of mortality. Conclusion: The response to the SARS‐CoV‐2 pandemic included changes in routine hospital operations that allowed for the provision of a sufficient level of care for patients with and without COVID‐19. Although blood type may play a role in COVID‐19 susceptibility, it did not seem to be associated with patient mortality.